Determinants of the Willingness to Pay for Solid Waste Recycling among Households in Ilemela, Tanzania - Stanslaus Rupia (Publikasi Indonesia, 2022)
This study aimed to investigate the determinants of willingness to pay for solid wastes recycling among households in Ilemela District, Mwanza-Tanzania. The study design was a cross-sectional survey design which was conducted among households residing in Ilemela District. A multistage sampling technique was useful for selecting representative samples from every ward. Structured questionnaires were used to obtain data from study participants. Data was analyzed using descriptive statistics, logistic regression was used in analyzing the factors influencing household’s willingness to pay for solid waste recycling and ordinary least square regression was used to estimate the effect of socio-economic factors on the amount households were willing to pay for solid wastes in Ilemela District. The findings of the study show that majority of households were not willing to pay for solid waste recycling in Ilemela District, Mwanza region.The willingness to pay for solid waste recycling was associated with age of the household head, marital status, and education. Information dissemination and logarithm of household’s income while the effect of socio-economic factors on amount households were willing to pay for solid waste recycling was associated with the marital status (married households), households’ years of education, information dissemination on solid waste recycling and logarithm of income was statistically significant in influencing the amount households are willing to pay for solid waste recycling. The study recommends that the government and other interested stakeholders on solid waste management should invest more on education and awareness about importance of waste management to the mass using different mechanisms.